Influence of nimodipine on elimination of soman in rabbit blood and distribution of [3H]soman in mice. - LI Jin-Tong; RUAN Jin-Xiu; YUAN Shu-Lan; ZHANG Zhen-Qing; SONG Zheng-Yan; WANG Xiao-Ying (Acta Pharmacologica Sinica; Vol 23, No 10 (October 2002): Acta Pharmacologica Sinica, 2016)
AIM: To investigate the effect of nimodipine on the elimination of soman in rabbit blood and distribution of [3H]soman in mice. METHODS: Chirasil capillary gas chromatographic analysis method with large volume injections was used to determine the concentration of C(+/-)P(-)soman in rabbit blood. [3H]soman trace method was used to study the effect of nimodipine on soman distribution in mice. RESULTS: Nimodipine (10 mg/kg, ip, 1 h pre-treated) could significantly reduce the concentration of C(+/-)P(-)soman in rabbit blood from (54+/-13) to (19+/-12) microg/L blood at 15 s after soman injection (43.2 microg/kg, iv). Nimodipine could increase clearance rate [CL(S)] from (20.8+/-1.5) to (31+/-11) mL/kg/s and reduce AUC of C(+/-)P(-)soman from (2.08+/-0.15) to (1.6+/-0.4) mg/s. Nimodipine (10 mg/kg, ip, 1 h pre-treated) treatment could significantly reduce the distribution amount of bound [3H]soman in plasma, brain, lung, and liver, moreover increased the distribution amount of bound [3H]soman in small intestine during 0-120 min after mice received [3H]soman (0.544 GBq*119 microg/kg, sc) compared to soman control group. CONCLUSION: Nimodipine might alter the distribution of soman and reduce the initial concentration of soman in rabbit blood, then accelerated the metabolic detoxication of soman.